Cell interactions in the immune response in vitro. 3. Specific collaboration across a cell impermeable membrane. - Feldmann, M; Basten, A (1972)
Tissue cultures with two compartments, separated by a cell impermeable nuclepore membrane (1 micro pore size), were used to investigate the mechanism of T-B lymphocyte cooperation. It was found that collaboration was as effective when the T and B lymphocyte populations were separated by the membrane as when they were mixed together. Critical tests were performed to verify that the membranes used were in fact cell impermeable. The specificity of the augmentation of the B cell response by various T cell populations was investigated. Only the response of B cells reactive to determinants on the same molecule as recognized by the T cells was augmented markedly. Specific activation of thymocytes by antigen was necessary for efficient collaboration across the membrane. The response of both unprimed and hapten-primed spleen cells was augmented by the T cell "factor" although, as expected, hapten-primed cells yielded greater responses. The T cell factor acted as efficiently if T cells were present or absent in the lower chamber. Thus the site of action of the T cell factor was not on other T cells, but was either on macrophages or the B cells themselves. The T cell-specific immunizing factor did not pass through dialysis membranes. The experiments reported here help rule out some of the possible theories of T-B cell collaboration. Clearly T-B cell contact was not necessary for successful cooperation to occur in this system. Possible theoretical interpretations of the results and their bearing on the detailed mechanism of T-B lymphocyte cooperation are discussed.